Analisis Penerapan Good Governance Dilihat Dalam Perspektif Permendikbud Nomor 6 Tahun 2021 - Bustanul Ulum; Dini Ayu Pramitasari; Anisaul Hasanah; Muhammad Halifatur Rahman (Sekolah Tinggi Ilmu Ekonomi NU Trate Gresik, 2022)
This study aims to examine and analyze the implementation of good governance in managing BOS funds at UPT SMP Negeri XYZ Gresik with the regulation of the Minister of Education and Culture Number 6 of 2021. This research uses a qualitative approach. Where qualitative research is rooted in a natural setting as a whole, relies on humans as research tools, conducts data analysis by drawing conclusions based on general conditions that occur at the research location. From the results of this study, information was obtained that the implementation of good governance in the management of BOS funds carried out at UPT SMP Negeri XYZ Gresik was not fully in accordance with The Minister of Education and Culture Number 6 of 2021, technical problems in the implementation of BOS fund management included delays in BOS technical guidelines, Application of Activity Plans and School Budgets (ARKAS). that cannot be accessed, delays in distributing BOS funds, delays in reporting on accountability for the use of BOS funds, but in terms of BOS budget performance after measuring the average results Good. The theoretical implication used in this research is agency theory and the principle of good governance of BOS funds in The Minister of Education and Culture Number 6 of 2021. While the practical implications of this research are the results of a comparison between the implementation of good governance principles contained in the Regulation of the Minister of Education and Culture Number 6 of 2021 with implementation at UPT SMP Negeri XYZ Gresik Country. Throughout the results of research observations to date, no research has been found regarding the application of the principles of good governance in managing BOS funds in the Regulation of the Minister of Education and Culture perspective.